2003
DOI: 10.1074/jbc.m303786200
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Histones Are Components of the Perinuclear Theca in Bovine Spermatozoa

Abstract: The perinuclear theca is a non-ionic detergent-resistant, electron-dense layer surrounding the condensed nucleus of mammalian sperm. The known proteins originating from the perinuclear theca have implicated the structure in a variety of important cellular processes during spermiogenesis and fertilization. Nonetheless, the composition of the perinuclear theca remains largely unexplored. We have isolated a group of low molecular mass (14 -19 kDa) perinuclear theca-derived proteins from acrosome-depleted bovine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
52
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 63 publications
(68 reference statements)
4
52
0
Order By: Relevance
“…4); this pattern was also similar to that reported in previous experiments in swines (Flores et al 2011) and humans (Zhang et al 2006). Additionally, one of the few immunocytochemical studies conducted on bull sperm chromatin has demonstrated that histones are also located in the perinuclear theca (Tovich & Oko 2003). This result is consistent with our findings, where we observed that the histone signals were mainly present in the pre-equatorial region of the sperm head.…”
Section: Discussionsupporting
confidence: 93%
“…4); this pattern was also similar to that reported in previous experiments in swines (Flores et al 2011) and humans (Zhang et al 2006). Additionally, one of the few immunocytochemical studies conducted on bull sperm chromatin has demonstrated that histones are also located in the perinuclear theca (Tovich & Oko 2003). This result is consistent with our findings, where we observed that the histone signals were mainly present in the pre-equatorial region of the sperm head.…”
Section: Discussionsupporting
confidence: 93%
“…The 2D basic protein system used in this study did not resolve and identify modified protamines because they are extremely basic and rich in disulphide bridges; however, histones were present on the gels. It is tempting to speculate that these may be residual nuclear histones, although somatic histones are known also to be present in the subacrosomal sheath of the perinuclear theca (PT) (Tovich and Oko, 2003). The PT, a specialized cytoskeletal structure under the acrosome and surrounding sperm nuclei, has been implicated in acrosome-nuclear docking and nuclear shaping during spermiogenesis (Aul and Oko, 2002;Oko, 1995), as well as in oocyte activation and pronuclear formation (Sutovsky et al, 1997;Kimura et al, 1998;Manandhar and Toshimori, 2003;Sutovsky et al, 2003); the potential exists for PT-derived histones to contribute to male pronuclear development.…”
Section: Discussionmentioning
confidence: 99%
“…sonication, Triton X-100, and alkaline carbonate, pH 11.5) were all able to trigger Ca 2ϩ oscillations comparable with those observed at natural fertilization. These investigators emphasized that only in the case of high pH treatment was the Ca 2ϩ releasing activity fully released indicating that the factor was most likely a PT component according to our definition (4,20). Perry et al (21) proposed a so-called trans-complementation scheme of sperm-borne oocyte activating factors, detailing that full oocyte activation and embryo development can be achieved only with the combination of a DTT-soluble fraction obtained from Triton-demembranated mouse sperm head and the heat-stable component of the head after DTT extraction.…”
mentioning
confidence: 96%
“…For example, alkaline extractable SubH2Bv, exclusive to the subacrosomal layer, is implicated in acrosome-nuclear docking during spermiogenesis (1). Salt-extractable non-nuclear somatic core histones, residing in the PAS, may be involved in stabilizing the chromatin of the decondensing sperm nucleus soon after oocyte entry (4,5). The DTT salt or alkaline extractable calicin and cylicin II share a basic pI with the histones and bind to actin in vitro (6 -8).…”
mentioning
confidence: 99%